NIMG-52. RADIATION-INDUCED VASCULAR MALFORMATIONS MIMICKING TUMOR IN MRI-BASED TREATMENT RESPONSE ASSESSMENT MAPS (TRAMs) - Zach, Leor (Neuro Oncol, 2017)
BACKGROUND: We have recently presented MRI-based TRAMs enabling efficient separation between tumor (contrast clearance >1hour post injection, blue) and treatment-effects (TEs, contrast accumulation, red), validated histologically in 51 resected patients reaching 92%/100% PPV/sensitivity to morphologically active tumor. This high selectivity stems from the ability of viable vessels in blue/tumor regions to efficiently clear contrast by 1hour, while damaged lumens in red/TEs regions are unable to, resulting in contrast accumulation. ~400 adult patients have been recruited to our studies in Israel since 2010. As the TRAMs cannot differentiate blood vessels from active tumor (both appearing blue), we studied whether radiation-induced cavernoma-like vascular malformations (RICMs) may mimic tumors in the TRAMs. METHODS: Cases in which the pre-surgical TRAMs were found false-positive for tumor were re-reviewed. For comparison, 2 patients with newly diagnosed cavernomas and 4 with treated AVMs were scanned by the TRAMs. One AVM underwent TRAMs-guided biopsies. RESULTS: Four cases of false-positive TRAMs showing RICMs in histology were found between 2010-2017: GBM post Stupp followed by Avastin+Rindopepimut, breast and NSCLC metastases post SRS, and resected NSCLC post SRS to the surgery site. The pre-surgical TRAMs of the GBM and post-resection NSCLC showed 2-3mm blue masses within larger thin blue rims. The metastases depicted thin blue rims surrounding red regions. Histology revealed clusters of connective tissue with multiple vessel-channels in all 4 cases, consistent with RICMs at various stages of tissue re-organization. The treated AVMs TRAMs showed mixed blue/red regions. Biopsies taken from blue regions revealed large vessels, some showing re-organization; red regions showed TEs. The cavernomas were depicted blue in the TRAMs. CONCLUSIONS: The TRAMs reliability in differentiating tumor from TEs has been validated histologically reaching PPV=92%. The presented findings suggest that RICMs, as other vascular-malformations, may mimic tumor (blue) in the TRAMs, thus explaining false-positive cases.